Medicinal Substance Detection from Archaeological Dental Calculus - Ambarioni, Agnes (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Dental calculus is mineralized dental plaque adhering to tooth surfaces. During the process of mineralization, materials from saliva and the oral cavity are preserved within its layers. Recently, the ability of preservation, withstand time and harsh environment, made dental calculus an emerging topic in archaeological studies. Through the advancement of technology, dental calculus offers a valuable resource for exploring past human behavior, including health, diet, and medicinal practices. Although the study of archaeological dental calculus has been ongoing for many years, investigations of medicinal compounds are still underexplored. This paper aims to identify and analyze the use of medicinal substance to gain valuable insights of past healthcare systems, treatment methods, and the interaction between medicinal substances and culture. Studies have revealed the presence of medicinal plants, animal products, minerals, and metabolites from ancient dental calculus. The discovery also led to the understanding of habitual and cultural practice such as treatments through special diets and the practice of trades. However, challenges still remain, including distinguishing between intentional and accidental substance use, overcoming gaps in historical records, and addressing the underrepresentation of specific regions and eras. These limitations highlight the need for future research so we can deepen our understanding of historical medicine, contribute to preserving cultural knowledge, and shaping modern pharmacological practices.